1994
DOI: 10.5006/1.3293542
|View full text |Cite
|
Sign up to set email alerts
|

Principal Factors Affecting Microbiologically Influenced Corrosion of Carbon Steel

Abstract: Laboratory-scale batch experiments (semicontinuously fed) were conducted using a two-level factorial experimental design to investigate principal factors and interactions affecting microbiologically influenced corrosion (MIC) of carbon (C) steel. Factors considered included the C source as chemical oxygen demand (COD), sulfate (SO 4 2-) concentration, calcium carbonate (CaCO 3 ) precipitation, and bacteria inoculation at 20°C. Yates' algorithm was applied to calculate main and interaction effects, and an empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The protective role of CaCO 3 was demonstrated by many authors. [30,31] For the interaction with bacteria, Peng et al [32] found less biofouling when solution was understaurated with CaCO 3 . Due to the relationship between pH, oxygen content and CaCO 3 deposition, less CaCO 3 deposition could be considered in deaerated condition (constant pH).…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of CaCO 3 was demonstrated by many authors. [30,31] For the interaction with bacteria, Peng et al [32] found less biofouling when solution was understaurated with CaCO 3 . Due to the relationship between pH, oxygen content and CaCO 3 deposition, less CaCO 3 deposition could be considered in deaerated condition (constant pH).…”
Section: Discussionmentioning
confidence: 99%
“…The biocorrosion process may be detected by a combination of observations: corrosion morphology, presence of microbial slime masses, presence of hydrogen sulphide and ferrous or ferric hydroxide as observed in anaerobic systems [6]. This process is of considerable concern because the sulphate-reducing activity of bacteria is thought to be responsible for >75% of the corrosion in productive oil wells and for >50% of the failures in buried pipelines [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated accelerated metal corrosion rates in the presence of microbial flora, 2b, 6 , while others have shown the opposite effect: that certain microbial biofilms are able to protect surfaces from corrosion 7 . Even the same bacterial species have been implicated as corrosive or protective, depending on the study conditions 8 .…”
Section: Introductionmentioning
confidence: 99%